2006
DOI: 10.1001/archinte.166.6.689
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Blood Glucose Monitoring Manual to Enhance Monitoring Adherence in Adults With Diabetes

Abstract: Background: Frequent blood glucose (BG) monitoring is a critical component of diabetes management, yet many barriers exist to consistent monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 23 publications
1
45
0
5
Order By: Relevance
“…Clearly, SMBG may not be useful to patients who lack the necessary skills and motivation. However, several studies that have tested randomised interventions in patients already using SMBG [5,6] found that training to improve their ability to make appropriate behavioural decisions in response to blood glucose readings resulted in better glycaemic control.…”
mentioning
confidence: 99%
“…Clearly, SMBG may not be useful to patients who lack the necessary skills and motivation. However, several studies that have tested randomised interventions in patients already using SMBG [5,6] found that training to improve their ability to make appropriate behavioural decisions in response to blood glucose readings resulted in better glycaemic control.…”
mentioning
confidence: 99%
“…Also, in the recently published PRISMA (Prospective, Randomized Trial on Intensive Self-Monitoring Blood Glucose Management Added Value in Non-Insulin Treated Type 2 Diabetes Mellitus Patients) trial, performance of structured SMBG was associated with better clinical outcomes (19). An older publication demonstrated similar findings in adults with type 1 and type 2 diabetes and reinforced the importance of providing patients with the tools to perform SMBG effectively (18).…”
Section: Evidence For Smbgmentioning
confidence: 92%
“…The STeP (Structured Testing Program) study in people with type 2 diabetes, as a useful example for a study on SMBG, demonstrated structured SMBG contributing significantly to the improvement in glycemic control and psychosocial functioning compared with enhanced usual care, including free blood glucose meters and strips (17,18). Also, in the recently published PRISMA (Prospective, Randomized Trial on Intensive Self-Monitoring Blood Glucose Management Added Value in Non-Insulin Treated Type 2 Diabetes Mellitus Patients) trial, performance of structured SMBG was associated with better clinical outcomes (19).…”
Section: Evidence For Smbgmentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed 18 relevant RCTs [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], some of which had not been included in previous meta-analyses [20][21][22][23][24][25]. Why do these trials not provide a reliable answer?…”
mentioning
confidence: 99%